Bibliometric Study of Systemic Risk in Banking Sector - Alfiana, Alfiana (The Eastasouth Management and Business, 2025)
This bibliometric study provides a detailed analysis of the literature on systemic risk in the banking sector, focusing on publications from 2015 to 2025. Using data sourced exclusively from Scopus, this study maps the intellectual landscape of systemic risk research, identifying the main contributors, thematic trends, and research collaborations across different countries. The analysis reveals a significant increase in research activity over the decade, with a notable emphasis on the integration of technologies like artificial intelligence and the increasing influence of fintech on systemic risk management. The study highlights the importance of global collaboration in addressing the challenges posed by systemic risks, which are inherently transnational in nature. Key research gaps identified include the need for further exploration into the regulatory impacts of fintech and the cross-border effects of systemic risks. The findings provide valuable insights for academics, policymakers, and practitioners involved in financial regulation and risk management, emphasizing the need for an integrated approach to tackle the complexities of systemic risks in the banking sector.